Strategies to Enhance or Maintain Motivation in Learning a Foreign Language - Ana Muñoz-Restrepo; Marta Ramirez; Sandra Gaviria (Profile Issues in Teachers' Professional Development, 2020)
Motivation is one of the most important factors in the enjoyment and success in learning any subject, especially a foreign language. Many students approach the learning of a language based on academic mandates, family impositions, job requirements, and so on. These non-intrinsic motivations make learning a more difficult, frustrating, and non-pleasurable experience, both for students and teachers. Therefore, skills in motivating learners should be seen as central to teaching effectively. In this article, we provide a series of strategies for teachers to gradually lead students from an extrinsic motivation to a more internal and autonomous motivation. This approach is framed within one of the most recent and well-known theories of motivation: self-determination theory.